THE EFFECTIVITY OF NATURAL DIETS OF Tubifex sp. AND Chironomus sp. LARVAE TOWARD GROWTH PERFORMANCE OF MANFISH (Pterophyllum scalare, Schultze 1823) FRY - Joshua Sahat H Sitohang; Agus Setyawan; Hilma Putri Fidyandini; Siti Hudaidah; Limin Santoso (University of Lampung, 2022)
Natural feed Tubifex sp. and larvae of Chironomus sp. proven to be able to improve growth performance in several types of ornamental fish. The purpose of this study was to evaluate the natural feeding of Tubifex sp. and larvae of Chironomus sp. to the growth rate of manfish fry (Pterophyllum scalare). This study used the Complete Randomized Design (CRD) with 4 treatments fish feed namely commercial feed PF 500 (A), Tubifex sp. 100% (B), Tubifex sp. 50% and larvae of Chironomus sp. 50% (C), and larvae of Chironomus sp. 100% (D). Fish used are 2-4 cm in size and weigh approximately 1-2 g. Fish distribute into 12 aquariums with a density of each aquarium of 1 fish/liter. The results showed the natural feeding of Tubifex sp. and larvae of Chironomus sp. Significantly able to improve the growth of manfish fry. Feeding in the form of 100% Tubifex sp. resulting in the highest growth performance in manfish fry reaching 2,914 g and 5,202 cm for absolute weight and absolute length, respectively. The survival rate of manfish fry in this study reached 100% for all treatments and controls. This research is expected to be one of the references for ornamental fish farmers in manfish seed feeding management.